The First Hurrah: Edmonton Elects a Mayor, 1983 - Lightbody, Jame (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
This article by a participant-observer describes the four-part winning electoral strategy of Laurence Décore who was elected the thirty-first mayor of Edmonton on 17 October, 1983. Since the war, Edmonton's local elections have been dominated by purely local "nonpartisan" slates and like-minded independents. The 1983 compaign represented a dramatic re-affirmation of anti-party sentiments in the municipal electoral process of the city.